2017
DOI: 10.1186/s13568-017-0378-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community compositions in the gastrointestinal tract of Chinese Mongolian sheep using Illumina MiSeq sequencing revealed high microbial diversity

Abstract: Chinese Mongolian sheep are an important ruminant raised for wool and meat production. However, little is known about the microbiota of the gastrointestinal tract (GIT) of Chinese Mongolian sheep. To increase our understanding of the microbial community composition in the GIT of Chinese Mongolian sheep, microbiota of five sheep is investigate for the first time using the Illumina MiSeq platform. High microbial diversity was obtained from the GIT, and the microbiota exhibited a higher biodiversity in the stomac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 58 publications
(72 reference statements)
18
37
0
2
Order By: Relevance
“…The current study revealed significant differences of the microbial community composition (the alpha diversity) in different sampling sources (the large intestine, small intestine, and feces) in two bat species ( R. sinicus and M. altarium ) although no significant variations of beta diversity were observed. These results were in line with the previous studies in mice (Gu et al., ; Pang, Vogensen, Nielsen, & Hansen, ; Weldon et al., ), pigs (Looft et al., ; Mu et al., ), and sheep (Zeng et al., ). Observed differences across the sampling sources may be caused by environmental heterogeneity in different intestinal compartments and niches, such as different oxygen exposure, pH, and substrate availability (Hao & Lee, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study revealed significant differences of the microbial community composition (the alpha diversity) in different sampling sources (the large intestine, small intestine, and feces) in two bat species ( R. sinicus and M. altarium ) although no significant variations of beta diversity were observed. These results were in line with the previous studies in mice (Gu et al., ; Pang, Vogensen, Nielsen, & Hansen, ; Weldon et al., ), pigs (Looft et al., ; Mu et al., ), and sheep (Zeng et al., ). Observed differences across the sampling sources may be caused by environmental heterogeneity in different intestinal compartments and niches, such as different oxygen exposure, pH, and substrate availability (Hao & Lee, ).…”
Section: Discussionsupporting
confidence: 91%
“…Gut microbiota is often called the "forgotten organ" in its symbiotic host (O'Hara & Shanahan, 2006) and plays essential roles in food digestion, energy harvest, metabolism, and immune training of its host (Donaldson, Lee, & Mazmanian, 2016;Hooper, Littman, & Macpherson, 2012;Hooper, Midtvedt, & Gordon, 2002;Qin et al, 2010;Turnbaugh et al, 2006;Velagapudi et al, 2010). In mammals, large-scale studies of gut microbiota have been conducted in humans (Huttenhower et al, 2012;Lozupone, Stombaugh, Gordon, Jansson, & Knight, 2012;Saraswati & Sitaraman, 2015;Yatsunenko et al, 2012), mice (Gu et al, 2013;Tanca et al, 2017), other domestic animals such as pigs (Mu, Yang, Su, Zoetendal, & Zhu, 2017) and sheep (Zeng et al, 2017), and to a lesser extent in wild animals, such as bats (Chiroptera). Bats have been largely overlooked in terms of their gut microbiota although they represent the second largest mammalian order and over 20% of mammal species (Simmons, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Results confirmed that the isolates were members of two major phyla namely Firmicutes (95.65%, the most dominant culturable rumen and dung microbiota) and Actinobacteria (4.35%) and three families Streptomycetaceae, Enterococcaceae and Bacillaceae. Our findings were parallel to those in earlier studies on microbiota from the gastrointestinal tract of ruminants [8,26] . Our results were also consistent with previous studies those isolated Bacillus species from the rumen, cow dung and Tibetan pig's intestine [27,28] .…”
Section: Discussionsupporting
confidence: 92%
“…) Conversely, when comparing adult nematodes with ovine abomasal washings, 2494 shared ASVs of a possible 6936 unique ASVs were identified across both groups. Samples clustered definitively based on the host animal of origin.Next, we reviewed several recent studies that have profiled the ovine microbiome at various sites in the digestive tract according to the abundances of endogenous bacteria present(28,29). We then examined our own nematode microbiome data for the presence of bacteriafound in sheep in relatively high abundances.…”
mentioning
confidence: 99%